Maternal parity and its effect on adipose tissue deposition and endocrine sensitivity in the postnatal sheep - Melanie Healy (Journal of Endocrinology, 2009)
Maternal parity influences size at birth, postnatal growth and body composition with firstborn infants being more likely to be smaller with increased fat mass, suggesting that adiposity is set in early life. The precise effect of parity on fat mass and its endocrine sensitivity remains unclear and was, therefore, investigated in the present study. We utilised an established sheep model in which perirenal-abdominal fat mass (the major fat depot in the neonatal sheep) increases approximately 10-fold over the first month of life and focussed on the impact of parity on glucocorticoid sensitivity and adipokine expression in the adipocyte. Twin-bearing sheep of similar body weight and adiposity that consumed identical diets were utilised, and maternal blood samples were taken at 130 days of gestation. One offspring from each twin pair was sampled at 1 day of age, coincident with the time of maximal recruitment of uncoupling protein 1 (UCP1), whilst its sibling was sampled at 1 month, when UCP1 had disappeared. Plasma leptin was lower in nulliparous mothers than in multiparous mothers, and offspring of nulliparous mothers possessed more adipose tissue with increased mRNA abundance of leptin, glucocorticoid receptor and UCP2, adaptations that persisted up to 1 month of age when gene expression for interleukin-6 and adiponectin was also raised. The increase in fat mass associated with firstborn status is therefore accompanied by a resetting of the leptin and glucocorticoid axis within the adipocyte. Our findings emphasise the importance of parity in determining adipose tissue development and that firstborn offspring have an increased capacity for adipogenesis which may be critical in determining later adiposity.